Carrier-envelope-phase measurement of few-cycle mid-infrared laser pulses using high harmonic generation in zno - Hollinger, Richard; Hoff, Dominik; Wustelt, Philipp; Skruszewicz, Slawomir; Zhang, Yinyu; Kang, Huipeng; Wuerzler, Daniel; Jungnickel, Tom; Dumergue, Mathieu; Nayak, Arjun; Flender, Roland; Haizer, Ludovit; et al. (Optics Express, 2020)
High-harmonic generation (HHG) in crystals offers a simple, affordable and easily accessible route to carrier-envelope phase (CEP) measurements, which scales favorably towards longer wavelengths. We present measurements of HHG in ZnO using few-cycle pulses at 3.1μm. Thanks to the broad bandwidth of the driving laser pulses, spectral overlap between adjacent harmonic orders is achieved. The resulting spectral interference pattern provides access to the relative harmonic phase, and hence, the CEP.
CRIS-Team Scopus Importer:2023-04-20